Ragna Crimson. 5 - Kobayashi, Daiki (Manga artist) (Square Enix Manga & Books, 2022)
"In this action-packed dark fantasy, humanity lives under the threat of annihilation by immensely powerful dragons. The dragon hunter Ragna embarks on a revenge-fueled quest to eliminate that threat once and for all!... Ragna and Crimson have fallen in with the Silverware Princess and her Argentum Corps, who are sheltering civilians fleeing from dragon attacks. The plan is to escort the refugees out of the country for safety, but it won't be an easy task. The Mad Maestro Dragon and the Explosive Dragon--two of the most powerful members of the Blood of the Wing--are leading an army of ten thousand dragons toward the Corps's base. A desperate battle is about to unfold!"--Provided by publisher.